ARCHITECTURAL PERSPECTIVE OF GENDER ROLE IN DIGITAL ERA - Wasilah,; Hildayanti, Andi (JURNAL SIPAKALEBBI, 2020)
Many influential architects—many of them female—have been able to change how the world sees architectural design and the built environment. Their works are masterpieces that have not only been able to transform how the world understands architecture, but have also forefronted gender equality. This study thus seeks to forefront the building design of female architects who have influenced world civilization. Using a case study method, this research explains the architectural flow adopted by women architects, as well as the function, design, and characteristics of their works. It shows that women such as Julia Morgan, Zaha Hadid, and Norma Merrick Sklarek have been able to balance and inform urban development around the world, providing role models for young female architects in the digital era . Publication Rationale: We desire to show that gender equality exists in the world of architecture, and that the works of female architects have been able to influence world civilization.